Experimental practice technoscience, alterontologies, and more-than-social movements - Papadopoulos, Dimitris (Duke University Press, 2018)
Decolonial politics of matter -- Biofinancialization as terraformation -- Ontological organizing -- Activist materialism -- Insurgent posthumanism -- Brain matter -- Compositional technoscience -- Crafting ontologies
Includes bibliographical references. - Description based on print version record
Keywords: Social movements; Technology / Social aspects; Discoveries in science / Social aspects; Philosophical anthropology; Financialization / Social aspects; Gesellschaft; Experiment; Politische Bewegung; Soziale Bewegung